O desenvolvimento da autonomia e o empoderamento de aprendizes de inglês instrumental no contexto de graduação de fronteira sul do Brasil - Coracini, Sandra Regina (Universidade do Vale do Rio dos Sinos, 2022)
English for Specific Purposes, also known in Brazil as Inglês Instrumental, or even the acronym in English, ESP, emerged worldwide in the 1960’s to fill a gap left by the General English in the development of the interaction aspects of the language – reading, writing, listening and speaking – directed to professional/occupational or academic purposes of learners from different areas of human knowledge. In the ESP approach, the decisions about pedagogical practices and the contents to be developed in a course should be programmed based on research of learning interests, needs or wishes of a specific group of learners. This study undertook an action research methodology by exploring pedagogical practices based on one critical analysis of the needs and desires which aimed to give learners more power of decision and freedom of choice in order to develop learners’ sociocultural autonomy in seeking English language learning in class and beyond. The study was taken in the curricular subject Inglês Instrumental at a target university course in a public university in the southern border region of Brazil. The critical needs analyses was taken in this study as a mediational tool to enable zones of proximal development, defined as metaphoric cognitive space (LANTOLF; THORNE, 2006), to the development of sociocultural autonomy and learners’ empowerment in the teaching and learning process. The research made use of the triangulation method to analyze data of the participants generated by multimodal narratives, semi structured oral interviews, questionnaires and class observations registered in a diary. The interpretive data analysis showed that pedagogical practices based on a critical needs analysis were efficient for mediation opportunities in zones of proximal development for learning, autonomy and empowerment in the practices applied by the teacher-researcher that contemplated the learning desires of the learners and, partially, for free activities chosen and applied by the students.
Keywords: Análise crítica de necessidades; Inglês para fins específicos; Zona de desenvolvimento proximal; Autonomia sociocultural; Inglês instrumental; Critical needs analysis; English for specific purposes; Zone of proximal development; Sociocultural autonomy; English for academic purposes; ACCNPQ::Lingüística, Letras e Artes::Lingüística